PKM Pelatihan Penyusunan Sintaks Pembelajaran pada Perangkat Kurikulum Merdeka di Sekolah Yayasan Kemala Bhayangkari Makassar - Khaidir Rahman; Nurmila; Akmal Hidayat; Lahming; Ervi Novitasari (Sakura Digital Nusantara, 2023)
The application of the independent curriculum in learning activities is mandatory at every independent level, which requires teachers to be able to develop their instruments and innovate learning strategies or syntax so that the learning atmosphere becomes more enjoyable, both indoors and while working on projects outdoors. The aim of this service is to provide understanding and skills to teachers in compiling the syntax of learning activities, starting with introductory activities, core activities, and closing activities. In this service activity, there are 3 stages carried out, namely: (1) preparation stage; (2) implementation stage; and (3) evaluation stage. After the training activities, it was seen that the teachers were very enthusiastic and understood the flow in creating learning syntax on the independent synchronization instrument. This made it easier for each teacher to design their learning activities to be more fun and measurable